Influence of maternal vitamin D status on obstetric outcomes and the foetal skeleton - Moon, Rebecca J (Eur J Endocrinol, 2015)
Vitamin D status is increasingly associated with wide ranging clinical outcomes. There is now a wealth of observational studies reporting on its associations with obstetric complications, including preeclampsia, gestational diabetes and mode and timing of delivery. The findings are inconsistent and currently there is a lack of data from high quality intervention studies to confirm a causal role for vitamin D in these outcomes. This is similarly true with regards to fetal development, including measures of fetal size and skeletal mineralisation. The available data justify the instatement of high-quality randomised placebo controlled trials in a range of populations and health care settings to establish potential efficacy and safety of vitamin D supplementation to improve particular outcomes.